2008
DOI: 10.1038/nsmb.1440
|View full text |Cite
|
Sign up to set email alerts
|

Capped small RNAs and MOV10 in human hepatitis delta virus replication

Abstract: The evolutionary origin of human Hepatitis Delta Virus (HDV) replication by RNA-directed transcription is unclear. Here we identify two species of 5′ capped, ∼18-25 nucleotide small RNAs. One was of antigenomic polarity corresponding to the 5′ end of Hepatitis Delta Antigen (HDAg) mRNA and interacted with HDAg and RNA POLYMERASE II (POL II), while the other mapped to a structurally analogous region on the genomic RNA hairpin. An HDAg-interaction screen uncovered MOV10, the human homologue of the A. thaliana RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 34 publications
2
73
0
Order By: Relevance
“…Interestingly, capped small RNAs (18-25 nt) have been recently detected and associated with HDV replication: one of antigenomic polarity has the same 5'-terminus as the ∂Ag-mRNA and interacts with ∂Ag and Pol II, while the 5'-terminus of the other maps at a structurally analogous region (the so-called pode) of the genomic RNA. 53 These capped small RNAs may well reflect the HDV transcription initiation sites, because typical Pol II transcripts are capped co-transcriptionally (incidentally, this rationale could be extended to members of the family Pospiviroidae, the transcription of which is also catalyzed by Pol II). In the proposed replication model, 53 annealed capped small RNAs would prime initiation of replication, given that primed HDV RNA-directed transcription has been observed in vitro.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, capped small RNAs (18-25 nt) have been recently detected and associated with HDV replication: one of antigenomic polarity has the same 5'-terminus as the ∂Ag-mRNA and interacts with ∂Ag and Pol II, while the 5'-terminus of the other maps at a structurally analogous region (the so-called pode) of the genomic RNA. 53 These capped small RNAs may well reflect the HDV transcription initiation sites, because typical Pol II transcripts are capped co-transcriptionally (incidentally, this rationale could be extended to members of the family Pospiviroidae, the transcription of which is also catalyzed by Pol II). In the proposed replication model, 53 annealed capped small RNAs would prime initiation of replication, given that primed HDV RNA-directed transcription has been observed in vitro.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…53 These capped small RNAs may well reflect the HDV transcription initiation sites, because typical Pol II transcripts are capped co-transcriptionally (incidentally, this rationale could be extended to members of the family Pospiviroidae, the transcription of which is also catalyzed by Pol II). In the proposed replication model, 53 annealed capped small RNAs would prime initiation of replication, given that primed HDV RNA-directed transcription has been observed in vitro. 44 Alternatively, synthesis of HDV RNA strands could be non-site-specific and primed by nascent host RNAs.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…Several lines of evidence implicate that MOV10 also affects a wide range of RNA viruses as a co-factor or restriction factor. For example, MOV10 is required for RNA-directed transcription in hepatitis delta virus (40), whereas it inhibits hepatitis C virus replication (41). Recently, several reports have demonstrated that MOV10 inhibits the replication of lentiviruses including human immunodeficiency virus type 1 (HIV-1).…”
mentioning
confidence: 99%
“…Recently, a hepatitis delta virus (HDV) small RNA of ~24-25 nt was reported to be expressed from the bottom strand of the antigenomic pode of the viral RNA genome (129) [pode and antipode refer to both extremities of the HDV RNA hairpin ends, excluded from the coding region of hepatitis delta antigen (HDAg)]. HDV is a subviral satellite that encodes for a single protein, the HDAg, and can propagate solely in the presence of hepatitis B virus (HBV) or in cells previously infected with HBV.…”
Section: Non-coding Rnas Expressed From Virusesmentioning
confidence: 99%